Program Peningkatan Kemampuan Public Speaking dan Mental Leadership bagi Siswa Sekolah Menengah : Speak to Lead - Tarigan, Fatin Nadifa; Nasution, Alwi Fahruzy; Ismayani; Siregar, Epi Supriyani; Fauzi, Fikriyah Iftinan (STMIK Triguna Dharma, 2025)
Program